Amnesty in the Age of Human Rights Accountability : Comparative and International Perspectives - Lessa, Francesca; Payne, Leigh A. (Cambridge : Cambridge University Press, 2012)
This edited volume brings together well-established and emerging scholars of transitional justice to discuss the persistence of amnesty in the age of human rights accountability. The volume attempts to reframe debates, moving beyond the limited approaches of 'truth versus justice' or 'stability versus accountability' in which many of these issues have been cast in the existing scholarship. The theoretical and empirical contributions in this book offer new ways of understanding and tackling the enduring persistence of amnesty in the age of accountability. In addition to cross-national studies, the volume encompasses eleven country cases of amnesty for past human rights violations: Argentina, Brazil, Cambodia, El Salvador, Guatemala, Indonesia, Rwanda, South Africa, Spain, Uganda and Uruguay. The volume goes beyond merely describing these case studies, but also considers what we learn from them in terms of overcoming impunity and promoting accountability to contribute to improvements in human rights and democracy.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Amnesty; Human rights; Liability (Law)